The Influence of Sustainable Leadership and Business Risk Management on Business Performance Mediated by Business Resilience in Restaurant Businesses in Medan - Fernando, Rosella; Masman, Ronnie Resdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Various risks can affect its performance. Restaurant owners and managers face increasingly complex challenges due to changes in the business environment, such as intense competition, market fluctuations, evolving consumer trends, and changing regulations. The purpose of this study is to determine whether sustainable leadership and business risk management impact business performance by enhancing business resilience in restaurant businesses in the city of Medan. The research method used is descriptive quantitative, with a sample size of 50. Data analysis was conducted using Partial Least Square (PLS). The results of the study indicate that sustainable leadership has a positive and significant influence on business resilience. Similarly, risk management also has a positive and significant influence on business resilience. While sustainable leadership positively influences business performance, this effect is not statistically significant. However, risk management has a positive and significant influence on business performance. Business resilience positively and significantly influences business performance, and both sustainable leadership and risk management positively and significantly influence business performance through business resilience as a mediator.